Górnoślązacy. Tożsamość regionalna i etniczna ponad granicami - Kijonka, Justyna (Człowiek i Społeczeństwo, 2017)
Silesian identity is what connects regardless of national identity. The aim of this article is to present the problem of identity of Upper Silesians living in Poland and in Germany in the context of conception of the imaginary community and transnational theory. The issues of the social worlds in which Upper Silesians live in Poland and in Germany will also be tackled. The paper is based on research devoted to the Upper Silesian identity, which I have been conducting for several years in Poland, and recently also in Germany.